Estimation issues and mathematical derivation of educational production function - Mohd Arshad, Mohd Nahar (IIUM, 2012)
A critical assessment of the extant literature of educational production function is discussed in this paper. The discussion covers two important aspects of research development in the area. First, the various approaches used in the estimation of educational production functions, their strengths and weaknesses, are analysed. The main objective of the exercise is to arrive at a shared understanding of the appropriate approach to modelling an educational production function. Second, the general relationship between the input and the output of education is identified from the extant literature. An identification of the relationship is instrumental in terms of variable selection for an empirical study. Once the underlying issues related to the estimation of educational production function are recognised, the derivation of three mathematical models of the function that can be applied in empirical works is provided.